2013
DOI: 10.1007/s10482-013-9984-3
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in diversity and community structure of endophytic bacteria and archaea across root, stem and leaf tissues in the common reed, Phragmites australis, along a salinity gradient in a marine tidal wetland of northern China

Abstract: Aims: The response of microbial metagenome to polycyclic aromatic hydrocarbons (PAHs) degradation in the rice rhizosphere remains poorly understood. We investigated the spatial and temporal variations of microbial communities and reconstructed metagenomes along the rice rhizosphere gradient during PAHs degradation. Methods and Results: The experiment was performed in rhizoboxes, in which the rhizosphere region was divided into five 1-mm thick layers. Based on denaturant gradient gel electrophoresis profiling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
26
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 60 publications
17
26
0
3
Order By: Relevance
“…These results extend current thinking, that multiple organisms within multiple taxonomic domains may be involved in the onset of disease or disease suppression in plants (Coats and Rumpho 2014). Most studies on microbial endophyte communities and dieback investigate one specific microbial taxon, typically fungi (Wilson and Pitkethley 1992;Diplock et al 2006;Kowalski and Holdenrieder 2009;Haque et al 2012;Ismail et al 2012;Sacdalan et al 2012), although there are exceptions (Mendes et al 2011;Knief et al 2012;Ma et al 2013;Oliveira et al 2013;Ruppel et al 2013). Our study found a very diverse microbial community (as assessed using OTUs) whose structure differed with plant health status.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These results extend current thinking, that multiple organisms within multiple taxonomic domains may be involved in the onset of disease or disease suppression in plants (Coats and Rumpho 2014). Most studies on microbial endophyte communities and dieback investigate one specific microbial taxon, typically fungi (Wilson and Pitkethley 1992;Diplock et al 2006;Kowalski and Holdenrieder 2009;Haque et al 2012;Ismail et al 2012;Sacdalan et al 2012), although there are exceptions (Mendes et al 2011;Knief et al 2012;Ma et al 2013;Oliveira et al 2013;Ruppel et al 2013). Our study found a very diverse microbial community (as assessed using OTUs) whose structure differed with plant health status.…”
Section: Discussionmentioning
confidence: 56%
“…At least for fungi, high endophytic fungal biodiversity has previously been observed in plants, which can host hundreds of fungal species or genotypes (Hawksworth 2001). High diversity of bacterial and archaeal endophytes is also expected (Ma et al 2013). Archaeal and fungal OTUs were twice as numerous per sample in dieback-affected plants compared to those in healthy plants.…”
Section: Discussionmentioning
confidence: 80%
“…This study showed that there were negligible differences in archaeal diversity among sampling sites or tissues of Phragmites australis (Ma et al 2013). Endophytic archaeal community was differentiated among sampling zones, but not among tissue types (Ma et al 2013).…”
Section: Discussionmentioning
confidence: 63%
“…In a previous study, Ma et al investigated the endophytic archaea in roots, stems and leaves of the common reed, Phragmites australis, using T-RF length polymorphism analysis of the 16S rRNA genes (Ma et al 2013). This study showed that there were negligible differences in archaeal diversity among sampling sites or tissues of Phragmites australis (Ma et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these soil bacteria are capable of penetrating the root, which is the main location of entry of bacterial endophytes ([ 12 ]. Ma et al [ 34 ] studied the diversity of endophytic bacteria in roots and leaves of the reed Phragmites australis under stressful saline conditions, and observed that the bacterial diversity in roots was significantly higher than that in the leaves.…”
Section: Sequencing and Diversity Overviewmentioning
confidence: 99%